Effect of Passage Smoothness on the Hydraulic Performance of Centrifugal Pumps - Garg, Sunil; Taneja, D S; Aggarwal, Rajan; Kaur, Samanpreet; Jamir, N I (Journal of Agricultural Engineering, 2007)
Improper passage smoothness in centrifugal pumps is one of the causes for their lower efficiency. The hydraulic characteristics of centrifugal pump due to application of the rubber paint on the inside and outside of the impeller and inside and outside of the impeller as well as inside of casing were studied. The efficiency improved upto 5.57 %, head increased upto 3.75 % and power requirement decreased upto 4.16 % after painting of impeller inside and outside. Similarly after painting of impeller (inside and outside) and inside of casing, improvement in etftciency was upto 12.33 %, head increased upto 7.09% and the power requirement decreased upto 15.09 %.